The Effect of Potassium Iodide Absorption on the Concentration of Antioxidants in Tomato Fruits - Kini, Medha; Flowers, Kate (Journal of Student Research, 2021)
Antioxidants are molecules found in fruits and vegetables that have the ability to fight substances in the human body that are detrimental to cells and genetic material. There is a high need for antioxidants, and the current method for boosting antioxidants is genetic modification, which is controversial in society; however, there is a lack of research concerning increasing antioxidant concentrations in plants in a natural manner. Thus, the efficacy of an iodine water drip can be called into question. Iodine has been proven to increase antioxidant enzymatic activity in animals and certain leafy vegetables. This paper will evaluate the effectiveness of an potassium iodide enriched water drip on the concentration of antioxidants in tomato plants. potassium iodide (KI) solution was created from diluting KI crystals into water, and the tomatoes were watered every day over a three month growth period. At the end of the allotted growth period, four tomatoes were plucked from each group—the potassium iodide group, and the control group that was watered regularly. In order to calculate the increase in concentration, each tomato was mashed with an Efferdent denture-cleansing tablet so as to measure the absorbance of each sample using the blue dye from the tablet. Once obtaining the absorbance, the concentrations were found using Beer’s law. Using a 2 sample T-test for the difference in antioxidants, the increase in antioxidants was found to be statistically significant.